Comparative study of online and offline learning results in Arabic course: Learning model in sustainability perspective - Agustien, Resi (INDONESIAN JOURNAL OF SUSTAINABILITY, 2023)
This study aims to compare online and offline learning results based on the analysis of students’ learning results in Arabic course. This study used a quantitative approach with a comparative method. Data collection was carried out after the online and offline learning process was completed in a different semester. The sample of this study was the grade one college students of Islamic Education majoring in FITK IBN Tegal. It consisted of 51 students from 2019/2020 year academic and 37 students from 2020/2021 year academic. It generated 88 students in total for the sample. The students enacted as the sample of research were grade one student, since the Arabic course as the research object was taught in grade one. The compared data research was students’ learning results on the 1st Arabic course. It encompassed four valuation components namely attendance, tasks, mid-term exam, and final exam scores compiled during online learning in 2019/2020 academic year and offline learning in 2020/2021 academic year. The data in the form of students’ scores were analyzed using normality, homogeneity, and t-test analysis technique. The result of this study shows that there is a difference in result scores in online and offline learning which shows the number of 06,58. Based on the result, it can be concluded that offline learning generates higher Arabic scores than online learning. Keywords: online learning; offline learning; comparison study